Sulang-Sulang Pomparan Ethnic Batak Toba Study: Oral Tradition - Nainggolan, Amoy Karamoii; Damanik, Ramlan; Sinaga, Warisman; Sinulingga, Sinulingga; Purba, Asriaty (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Sulang-sulang pomparan (tradition of feeding parents) is a family tradition carried out as a form of respect for both parents, usually when one of the parents is sick or critical. This study aims to describe the stages, performance (text, co-text and context) and values of oral tradition contained in the Sulang-sulang pomparan Ethnic Batak Toba. The theory used in this study is the theory of local wisdom proposed by Robert Sibarani (2014). The method used in the study is a qualitative method that is descriptive. The stages in the Sulang-sulang pomparan Ethnic Batak Toba are divided into two stages, namely the stages before which include: 1) The Sirarion Fellow (Discussion) between siblings and the stages of implementing the tradition which include: 1) Worship Event,2) Mampasahat Tudu-tudu Sipanganon Sian Sude Pomparan Event, 3) Manulangi Sian Sude Pomparan Event, 4) Mampasahat Dengke, Ulos, Dohot Manulangi Sian Hula-hula/Paraman Event. Performance in this tradition is divided into three parts, namely: 1) Text analysis, 2) Co-text analysis, and 3) Context analysis. The values in this tradition include: 1) Religious values / gratitude, 2) Cooperation values, 3) Art values, 4) Politeness values, 5) Social solidarity, 6) Gender management, 7) Harmony and conflict resolution attitudes, 8) Environmental care.